CTPAT dan Global Supply Chain Security - Ika Riswanti Putranti; Nur Adian Harisanto (Journal of Diplomacy and International Studies, 2019)
Supply chain security is one of the most integral aspect in global trade. The flow of goods or logistic through land, sea, and air transportation should be granted for its security. But with many Terrorism issue and accident pose a threat to supply chain because terrorism can destroy the flow chain of goods. United States then come as a pioneer in enforcing supply chain security through a program called CTPAT which focused on controlling and exmanining incoming cargo to US by US Custom and Border Protection (incoming import products). But what makes it interesting is, this program can enforce and strengthen global supply chain security. This research was meaning to explain how far is actor’s role in enhancing global supply chain security through CTPAT using complex interdependence where CTPAT is a public private partnership which makes private sector is considered into having role in enhancing global supply chain security. This research argue that actors role in enhancing global supply chains security is determined by benefits that actor’s gain in CTPAT Partnership and also because the emerging of terrorist threat to supply chain security which also included in CTPAT.